The Use Of A QR Code On A Notary Deed Is A Manifestation Of The Obligations Of A Notary Under The Law - Widi Nugrahaningsih (Veteran Justice Journal, 2020)
The rampant fraud in society, especially the existence of parties claiming to be notaries (being fakenotaries) and making deeds occur in the community and are very disturbing, have occurred in several areas,one of which is in Sleman. The problem that is taken from this research is whether the benefits of usingQuick Response code (QR code) in making a notary deed? The purpose of this research is to find outinformation about the benefits of QR codes in making notarial deeds in order to provide securityguarantees for the parties in the notarial deed. The research method is descriptive and explanatoryresearch, the research approach used is empirical, the types and sources of data from primary andsecondary data. While the data collection technique is by means of interviews (interviews with notarieswho have used the QR code on the deed they have made), direct observation (by looking at the forms ormodels of deeds made) and literature study. Data collection techniques with data reduction steps, datapresentation, drawing conclusions. The conclusion from the research is that the use of QR Code in makingnotarial deeds does not violate the provisions of the Law, even in accordance with Article 16 paragraph (1)letter g UUJN-P, that notaries are obliged to act honestly, thoroughly, independently, not taking sides, andprotecting interests. the parties involved in legal action.